Debating Balkan commonalities: Is there a common Balkan culture? - Markovich Slobodan G. (Balcanica)
Analysing the contributions of Jovan Cvijić, Traian Stoianovich, Paschalis Kitromilides and a range of Balkanologists, the author attempts to summarise the debate on Balkan commonalities and answer if the debate was able to identify shared features that could be seen as a common Balkan culture. The author first deals with the emergence of Balkan studies, which he connects with the spirit of regional cooperation that appeared in the Balkans after 1928. The first efforts to answer the question of Balkan commonalities were made in the seminal work of this discipline on the Balkan Peninsula (1918). In this book, Jovan Cvijić provided evidence for a divided rather than a unified region. The efforts of Traian Stoianovich to define a “Balkan civilization” remained in the borderland between global history and Balkanology. Paschalis Kitromilides provided the most convincing arguments for a Balkan mentality but did not go beyond the early modern period and Balkan Orthodox Christians. In the paper the evolution of the term Balkanism has been analysed to retrace the change of focus in Balkan studies, which lost some its original drive from the 1930s for finding commonalities, instead growing more focused on political and cultural contexts. In the conclusion the importance of the whole debate on Balkan commonalities has been highlighted. Although strong evidence of Balkan commonalities was found only in linguistics, this discussion proved significant for Balkan studies and brought about important results for the discipline.